Nonlinear Model for Lead Rubber Bearings Including Axial Load Effects and Large Deformations - Moussa, L.; Ali, Z.; Abdelkader, B.; Rahman, Muhammad (IRED, 2014)
Several nonlinear models have been developed to simulate the behavior of single isolation bearings. However, these models neglect certain aspects of bearing response behavior. For instance, rubber bearings have been observed to decrease in both elastic and post-elastic stiffness with increasing axial load, and soften in the vertical direction at large deformations. In this paper a macro-element model for lead rubber bearings is developed. The proposed model includes axial load effects and accounts for large deformations. The nonlinearity in the model is modeled via the Bouc-Wen model of hysteresis. Response obtained using the numerical model is shown to be in good agreement with observed behavior in test results on single lead rubber bearings. A stability analysis on a Lead-Rubber Bearing is then conducted to investigate the accuracy of the proposed macro-element on capturing the effect of axial loads.